The Improvement of Service Quality Using Importance Performance Analysis case Study PDAM Cianjur - Taufiq Dwi Jatmika, Rahmat; Febriansyah, Hary (The Indonesian Journal of Business Administration, 2016)
Abstract - The development of the business more rapidly and is very competitive give an impact to the company to give the best quality to the customers. Customers can have a considerable influence on the performance of the company. The company's interaction with customer not only exchange products and services only. Complaints and comment from the customers can provide feedback that is positive for the company. Some customers have a higher expectation of the quality of services rendered by the company. Given these interrelationships, the quality of the products and services provided by the company will increase. Therefore, the purpose of this study was to determine the level of customer satisfaction with the quality of service provided by PDAM Cianjur. In this study, research performed using SERVQUAL method, where there is gap between performance and importance to measure the level of customer satisfaction on the quality of services rendered by the company. IPA Matrix is used to determine the results of the SERVQUAL that indicates part of the quality of services must be improved in order to give satisfaction to the customer. Based on the analysis of SERVQUAL are five problems that occur. Based on internal and external conditions, taps has made improvements without notice from the customer's perspective. The performance generated by PDAM is still lacking in terms of the company's facilities, the availability of information, the availability and readiness of service, and technology used to facilitate the customers.Â Keywords: Customer satisfaction, the quality of service, SERVQUAL, IPA Matrix